Does Consumer Like the Coffee? A Study of Product Quality of a Local Business Ground Roasted Coffee in North Sumatera - Wiyono, Sulistyodewi Nur; Utami, Hesty Nurul; Kamarulzaman, Nitty Hirawaty (Universitas Pendidikan Ganesha, 2024)
Producers are required to provide quality products according to quality standards and consumer needs. Quality is one factor that consumers consider when buying a product. The coffee processing industry is rapidly growing because of the high demand for this product.